The feasibility and farmer perception of true shallot seed technology in Sigi District, Central Sulawesi, Indonesia - RAHAYU, HENI SP; MUCHTAR, MUCHTAR; SAIDAH, SAIDAH (Asian Journal of Agriculture, 2019)
Abstract. Rahayu HSP, Muchtar, Saidah. 2019. The feasibility and farmer perception of true shallot seed technology in Sigi District, Central Sulawesi, Indonesia. Asian J Agric 3: 16-21. Shallot is one of horticultural commodities that plays a significant role in both national and regional economy. A fluctuating supply of shallot influences the inflation level. Shallot production is currently still facing many problems, including high production cost. The high shallot production cost mostly goes to expenses for labor and seed while Indonesian shallot is mainly produced from the bulbs seed. This high-cost production causes a lower shallot competitiveness. Therefore, introduction of True Shallot Seed (TSS) technology, which lowers the cost for shallot seed, could be an ideal option to improve the shallot competitiveness in Indonesia. However, the shallot farming feasibility and the farmer’s perception of this technology are two critical aspects that need to be considered in the adoption of this new technology. This research aimed to study the potency of true shallot seed development in Central Sulawesi based on the TSS’s farming feasibility and farmer perception on TSS. The research was conducted in Sigi District, Central Sulawesi. The results showed that the farming of shallot using TSS was feasible, and within 14.9 t.ha-1 productivity, the Revenue-Cost Ratio was 3.15 while the Benefit-Cost Ratio was 2.15. The perception was examined based on three aspects namely technical, economic, and social aspects. The results showed that farmers were interested in planting true seed of shallot based on its high productivity, lower production cost, and market acceptance of the product; while in the social aspect, the extension and farmer group’s support still need to be improved for development of TSS.